(untitled) (Islas, 2018)
Dada la necesidad de crear un vínculo entre el patrimonio tangible e intangible dentro del proyecto de Regeneración 2017 y así aumentar el carácter cultural del eje Boulevard de Santa Clara, se realiza un estudio del inmueble de la tienda «El Arco» en busca de criterios para la rehabilitación de un edificio con valores patrimoniales como Casa de la Trova para el desarrollo e impulso de una manifestación de la cultura que se ha convertido en parte del patrimonio intangible de la ciudad de Santa Clara. Given the need to create a link between the tangible and intangible heritage within the Regeneration 2017 project and thus increase the cultural character of the Boulevard axis of Santa Clara, a study of the «El Arco» storehouse is carried out in search of criteria for the rehabilitation of a building with heritage values such as Casa de la Trova for the development and promotion of a manifestation of the culture that has become part of the intangible heritage of the city of Santa Clara.